Development of bifurcated current sheets in solar wind reconnection exhausts. Issue 24 (19th December 2015) - Mistry, R.; Eastwood, J. P.; Phan, T. D.; Hietala, H.
Abstract: Petschek‐type reconnection is expected to result in bifurcations of reconnection current sheets. In contrast, Hall reconnection simulations show smooth changes in the reconnecting magnetic field. Here we study three solar wind reconnection events where different spacecraft sample oppositely directed reconnection exhausts from a common reconnection site. The spacecraft's relative separations and measurements of the exhaust width are used to geometrically calculate each spacecraft's distance from the X line. We find that in all cases spacecraft farthest from the X line observe clearly bifurcated reconnection current sheets, while spacecraft nearer to the X line do not. These observations suggest that clear bifurcations of reconnection current sheets occur at large distances from the X line (~1000 ion skin depths) and that Petschek‐type signatures are less developed close to the reconnection site. This may imply that fully developed bifurcations of reconnection current sheets are unlikely to be observed in the near‐Earth magnetotail. Key Points: Three events where both of the oppositely directed exhausts are observed Exhausts encountered farther from the X line show clear bifurcations Bifurcations may be fully developed ~1000 ion skin depths downstream